Involvement and barriers to research amongst students of Khyber Medical College - Shahab, Faseeh; Ali, Mahrukh Ayesha; Hussain, Hamid (Journal of Postgraduate Medical Institute, 2013)
Objectives: To find the involvement in research amongst students of Khyber Medical College and to identifyreasons for not doing research. Methodology: A cross-sectional study was performed in which medical students (n=160) from differentyears of study were asked to fill a questionnaire. Stratified random sampling was done as 20 male studentsand 20 female students from each year answered the 10-question. Total positive score was calculated. Results: One-hundred and sixty students completed the survey. There were equal male and female respondents(80 each). The students were from 2nd, 3rd, 4th and final year. Among the respondents, only fifteen(9%) were involved in a research project; one hundred and thirty students (81.2%) believed that researchis easy if proper guidance is given. One hundred and one students (63%) thought that research couldenhance understanding of the subject. Most students disagreed with the idea that research could only bedone by intelligent students (139, 86.8%). One hundred and forty students (87.5%) replied that they areinterested in doing research, provided proper guidance is given. Conclusion: In this study, we found out that very few students of Khyber Medical College are involved inresearch. Lack of awareness regarding importance of research and lack of guidance for undertaking researchwere identified as main barriers for doing research. The concerned authorities need to take stepsto encourage students and should involve teachers to streamline the process.Objectives: To find the knowledge and attitude of medical students of Khyber Medical College towards research and to determine barriers for not doing research. Material and methods: A cross-sectional study was performed in which medical students (n=160) from different years of study were asked to fill a questionnaire. Stratified random sampling was done as 20 male students and 20 female students from each year answered the 10-question questionnaire. Total positive score was calculated. Results: One-hundred and sixty students completed the survey. There were equal male and female respondents (80 each). The students were from 2nd, 3rd, 4th and final year. Among the respondents, only fifteen (9%) were involved in a research project; one hundred and thirty students (81.2%) believed that research is easy if proper guidance is given. Sixty-nine students (43.1%) answered that there are no research activities going on in KMC. One hundred and one students (63%) thought that research could enhance understanding of the subject. Most students disagreed that research could only be done by intelligent students (139, 86.8%). One hundred and forty students (87.5%) replied that they are interested in doing research, provided proper guidance is given. Conclusion: In our survey, we found out that the students of Khyber Medical College are interested in learning about health system research and doing it but there is no proper guidance. The concerned authorities need to take steps to encourage students and should involve teachers to streamline the process.